O DIÁLOGO SOCIAL NO SUPREMO TRIBUNAL FEDERAL E A EFETIVAÇÃO DO DIREITO À SAÚDE VIA PODER JUDICIÁRIO: VOZES DA AUDIÊNCIA PÚBLICA - Fogaça, Vitor Hugo Bueno (2014)
This study has as object the process of improvement of the health right by the Judiciary, whose understanding has derived from the discussions brought in the public hearing of health held by the Federal Supreme Court in 2009. In this sense, your overall goal is to analyze the arguments brought in the audience, comparing them to synthesize the thought of the orators regarding the effectuation process of health policies through the judicial assistance process. It is an interdisciplinary exploratory research that promotes a qualitative analysis of the orators speeches at the event held by the Federal Supreme Court through the content analysis method. The methodological procedures involved were the bibliographic and documentary research. The study was organized in four chapters. The first chapter seeks to elucidate the methodological trajectory adopted in the research construction, including the exposure of the ideals that inspired their subject and their justifications and objectives. The second chapter, entitled "Relevant aspects of Brazilian constitutional order: social fundamental rights, the Federal Supreme Court and public hearing in the Judiciary" is composed of reflections on the Brazilian legal system, fundamental rights and the Federal Supreme Court, whose acting permeates problems of work. "The fight for health, the Brazilian sanitary movement and the denial of a fundamental right: the judicialization of public health policies in Brazil" brings in the third chapter the trajectory of health in Brazil, as well as the composition and directives of the SUS, whose content turned out to unleash the phenomenon of judicialization. Finally, in the fourth chapter, "Voices of the public hearing: the realization of the right to health by Judiciary", are presented and discussed the arguments brought by 49 orators, categorized by content analysis, getting up the problem of ensuring the right to health via the judiciary. What is more evident in the survey is the difficulty in establishing truly answers to ethical dilemmas that go beyond the mere hermeneutics of legal rules, however, the work seeks to identify the parameters constructed from the analysis of the discussion of the public hearing, to subsidize debate and the judgment of lawsuits involving the health service.